Do changing medical admissions practices in the UK impact on who is admitted? An interrupted time series analysis. Issue 10 (8th October 2018) - Fielding, Shona; Tiffin, Paul Alexander; Greatrix, Rachel; Lee, Amanda J; Patterson, Fiona; Nicholson, Sandra; Cleland, Jennifer
Abstract : Introduction: Medical admissions must balance two potentially competing missions: to select those who will be successful medical students and clinicians and to increase the diversity of the medical school population and workforce. Many countries address this dilemma by reducing the heavy reliance on prior educational attainment, complementing this with other selection tools. However, evidence to what extent this shift in practice has actually widened access is conflicting. Aim: To examine if changes in medical school selection processes significantly impact on the composition of the student population. Design and setting: Observational study of medical students from 18 UK 5-year medical programmes who took the UK Clinical Aptitude Test from 2007 to 2014; detailed analysis on four schools. Primary outcome: Proportion of admissions to medical school for four target groups (lower socioeconomic classes, non-selective schooling, non-white and male). Data analysis: Interrupted time-series framework with segmented regression was used to identify the impact of changes in selection practices in relation to invitation to interview to medical school. Four case study medical schools were used looking at admissions within for the four target groups. Results: There were no obvious changes in the overall proportion of admissions from each target group over the 8-year period, averaging at 3.3% lower socioeconomic group, 51.5% non-selective school, 30.5% non-white and 43.8% male. Each case study school changed their selection practice in decision making for invite to interview during 2007–2014. Yet, this within-school variation made little difference locally, and changes in admission practices did not lead to any discernible change in the demography of those accepted into medical school. Conclusion: Although our case schools changed their selection procedures, these changes did not lead to any observable differences in their student populations. Increasing the diversity of medical students, and hence the medical profession, may require different, perhaps more radical, approaches to selection.